Human surveillance and phylogeny of highly pathogenic avian influenza A(H5N8) during an outbreak in poultry in South Africa, 2017. Issue 3 (14th February 2020) - Valley‐Omar, Ziyaad; Cloete, Alicia; Pieterse, Reneé; Walaza, Sibongile; Salie‐Bassier, Yusrah; Smith, Mikhail; Govender, Nevashan; Seleka, Mpho; Hellferscee, Orienka; Mtshali, Phillip Senzo; Allam, Mushal; Ismail, Arshad; et al.
Abstract: Background: In June 2017, an outbreak of the highly pathogenic avian influenza A(H5N8) was detected in commercial poultry farms in South Africa, which rapidly spread to all nine South African provinces. Objectives: We conducted active surveillance for the transmission of influenza A(H5N8) to humans working with infected birds during the South African outbreak. Methods: Influenza A(H5N8)‐positive veterinary specimens were used to evaluate the ability of real‐time PCR‐based assays to detect contemporary avian influenza A(H5N8) strains. Whole genome sequences were generated from these specimens by next‐generation sequencing for phylogenetic characterization and screening for mammalian‐adaptive mutations. Results: Human respiratory samples from 74 individuals meeting our case definition, all tested negative for avian influenza A(H5) by real‐time PCR, but 2 (3%) were positive for human influenza A(H3N2). 54% (40/74) reported wearing personal protective equipment including overalls, boots, gloves, masks, and goggles. 94% (59/63) of veterinary specimens positive for H5N8 were detected on an influenza A(H5) assay for human diagnostics. A commercial H5N8 assay detected H5 in only 6% (3/48) and N8 in 92% (44/48). Thirteen (13/25; 52%) A(H5N8) genomes generated from veterinary specimens clustered in a single monophyletic clade. These sequences contained the NS (P42S) and PB2 (L89V) mutations noted as markers of mammalian adaptation. Conclusions: Diagnostic assays were able to detect and characterize influenza A(H5N8) viruses, but poor performance is reported for a commercial assay. Absence of influenza A(H5N8) in humans with occupational exposure and no clear impression of molecular adaptation for mammalian infection suggest that this avian pathogen continues to be low‐risk human pathogen.